Antidepressant activity of Citrus limetta leaves in mice using battery of behavior models modulating via serotonergic systems (Bangladesh Journal of Pharmacology, 2019)
The methanolic extract of Citrus limetta leaves was estimated in the present study for antidepressant activity. This activity was evaluated by using the rat behavioral model i.e. forced swimming and tail suspension model for 14 days, with estimation of neurotransmitters in animals brain. The sedative effect was evaluated by actophotometer. The extract (200 mg/kg) administered orally showed significant (p